Pulmonary sarcoidosis with lung injury induced by shin’iseihaito: Shin’iseihaito-induced sarcoidosis - Suzuki, Kentaro; Kai, Yoshiro; Matsuda, Masayuki; Horimoto, Kazuhide; Iwai, Kazonori; Hamada, Eriko; Yamamoto, Yoshifumi; Takano, Masato; Muro, Shigeo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis is a multisystemic granulomatous disease of unknown cause. A 72-year-old man with a history of cerebral infarction presented with dyspnea after 3 weeks of smoking cessation treatment with shin’iseihaito. He was referred and admitted to our hospital for further investigation and treatment. Chest computed tomography revealed a lung infiltrative shadow, primarily in bilateral upper lobes, and enlargement of mediastinal and bilateral hilar lymph nodes. First, drug-induced lung injury by shin’iseihaito was suspected; shin’iseihaito was discontinued. However, chest imaging findings did not improve. On day 7, bronchoalveolar lavage fluid revealed 90% macrophages, 5% lymphocytes, and an increased CD4/CD8 T-cell ratio. Transbronchial lung biopsy histological findings showed inflammatory infiltrate and noncaseating granuloma, and in ophthalmologic survey, bilateral panuveitis was observed. The drug lymphocyte stimulation test for shin’iseihaito was negative. These findings suggested the diagnosis of pulmonary sarcoidosis induced by shin’iseihaito. He was treated with systemic steroids, resulting in improvement in radiological findings. He was discharged on the 21st day. Follow-up chest X-ray images after discharge confirmed the absence of recurrence. Very few cases of pulmonary sarcoidosis with acute injury have been reported. To our knowledge, this is the first case report of pulmonary sarcoidosis induced by herbal medicines, such as shin’iseihaito. Pulmonary sarcoidosis and drug-induced lung injury should be considered as a differential diagnosis in lung injury shadow during the administration of herbal medicine including shin’iseihaito.